2021
DOI: 10.23889/ijpds.v5i4.1695
|View full text |Cite
|
Sign up to set email alerts
|

population level study of SARS-CoV-2 prevalence amongst people experiencing homelessness in Wales, UK

Abstract: IntroductionPrior research into the prevalence of SARS-CoV-2 infection amongst people experiencing homelessness (PEH) largely relates to people in communal forms of temporary accommodation in contexts where this type of accommodation remained a major part of the response to homelessness during the COVID-19 pandemic. Little is known about the prevalence of SARS-CoV-2 amongst PEH more broadly, and in a policy and practice context that favoured self-contained accommodation, such as Wales, UK. ObjectiveDescribe th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 34 publications
(45 reference statements)
3
14
0
Order By: Relevance
“…Our results are in line with a population level study from Wales, UK showing lower PCR positivity among PEH as compared to the general population (9). The authors explain this nding by a proactive policy response directing local authorities on sourcing additional temporary accommodation for PEH, including, for instance, hotels and bed and breakfasts accommodation and adapted night-shelters, a situation comparable to the Netherlands.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Our results are in line with a population level study from Wales, UK showing lower PCR positivity among PEH as compared to the general population (9). The authors explain this nding by a proactive policy response directing local authorities on sourcing additional temporary accommodation for PEH, including, for instance, hotels and bed and breakfasts accommodation and adapted night-shelters, a situation comparable to the Netherlands.…”
Section: Discussionsupporting
confidence: 90%
“…A study conducted across nine Dutch cities during the rst wave reported a SARS-CoV-2 PCR positivity rate of 17% among PEH with COVID-related symptoms or who had a close contact with individuals with COVID-19 and visited the 'street doctors' (7), which was higher than the rate found among the general population during that period (8). In contrast, a population-based study from Wales, United Kingdom (UK) using routinely collected administrative data found that the SARS-CoV-2 PCR positivity rate among PEH was comparable to that of the general population (5.0% versus 5.6% between March 2020 and March 2021) (9). The authors suggest that this low percentage may have been due to the policy pandemic response for PEH, moving away from communal accommodation to offering PEH private rooms to reduce the risk of SARS-CoV-2 transmission(9).…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Specific settings, including emergency shelters and those with overcrowding or communal sleeping arrangements, are associated with increased risk of infection, presumably due to greater exposure during outbreaks compared with PEH living outdoors or in private and/or well distanced accommodations 15–18 24–27. In Wales, where PEH were comprehensively housed in private settings during the pandemic, COVID-19 prevalence was lower than in the general population 30. Similarly, shelters implementing physical distancing practices have been shown to have lower infection rates 15.…”
Section: Background and Rationalementioning
confidence: 99%
“… 15–18 24–27 In Wales, where PEH were comprehensively housed in private settings during the pandemic, COVID-19 prevalence was lower than in the general population. 30 Similarly, shelters implementing physical distancing practices have been shown to have lower infection rates. 15 Evidence for other individual-level or shelter-level factors associated with COVID-19 infection remains to be established, and effectiveness of most interventions remain to be evaluated.…”
Section: Background and Rationalementioning
confidence: 99%